Rancang Bangun Sistem Repositori Berbasis Web Semantik Menggunakan Ontologi - Dipati Bangsa, Prianda; Hermawan, Indra (Jurnal Teknologi Terpadu, 2020)
A repository is a system used to store data in the form of information such as archival documents, journals, or papers in an institutional institution. In this research, a repository system design will be made for the Department of Informatics and Computers at the Jakarta State Polytechnic based on the semantic web. Semantic technology allows the system to understand the meaning of information. This repository uses apache jena fuseki as data storage with SPARQL, which is made with the Resource Description Framework scheme. The final result of this research becomes a repository system that has been successfully applied to the final project collection in 2020 with regular and specific search features to facilitate the search for a document